Potencial turístico del “Qhapaq ñan” de la parroquia Cojitambo, para el desarrollo local del cantón azogues - Paúl Renato, Guallpa Guallpa (2022)
ABSTRACT: The objective of this research is to analyze how the tourism potential of the Qhapaq Ñan of the Cojitambo parish influences local development in the Azogues canton. To this end, a diagnosis of the supply and characterization of the tourism demand made, and then local development strategies proposed according to the reality identified in the territory. The research is documentary, descriptive, correlational and field research. The research design is non-experimental since no data of the study variables deliberately manipulated; at the same time, it is transversal because the data collected at a single moment, its purpose is to describe the variables and analyze them in a single place and in a specific period where the information collected. Thus, 330 surveys administered to visitors arriving in the Cojitambo parish, where the Qhapaq Ñan is located, 196 surveys administered to the inhabitants of Cojitambo, and 78 surveys administered to service providers in the city of Azogues, the closest town to the Qhapaq Ñan that offers tourism services. The reliability of the instrument measured by applying Cronbach's Alpha coefficient. Descriptive analyses also carried out using tables and graphs, multiple correspondence analysis and word cloud analysis for data obtained in open or opinion questions, and the hypotheses tested using the J-square statistical method, which allowed us to test the independence of discrete qualitative variables. Finally, local development strategies elaborated, taking into account the tourism reality of the Qhapaq Ñan, the relevant characteristics of the demand and identified segments; in this way, two strategies proposed, the first is the strengthening of the local population's capacities through entrepreneurship, and the second is the creation of tourism routes, based on the visit to the Qhapaq Ñan. KEY WORDS: Tourism potential, local development, Qhapaq Ñan, local development strategies.